Post-COVID-19 American Religion: Congregational Crisis, Opportunity, and Innovation - L. Norton, Allison (KnE Social Sciences, 2024)
This paper explores the changing nature of congregations in the United States in a post-pandemic era, presenting a sociological analysis of crisis and opportunity. Drawing on insights from the expansive, five-year study – Exploring the Pandemic Impact on Congregations (EPIC) – the author focuses on the relationship between technology, innovation, optimism, and congregational life. The study asks how congregations can adapt and advance in the rapidly changing (digital) world, with its embrace of new internet technologies that have profoundly disrupted the “normal” ways of doing religion. The framework for understanding change draws on Scott Galloway’s twin theses that the pandemic has (1) acted as an accelerant to existing trends, both positive and negative, and (2) that the more disruptive the crisis, the greater the potential opportunity. Implications from the research not only for religious communities, but also educators, administrators, and leaders from various industries are discussed. Keywords: America religion, COVID-19, congregational crisis